Effect of Two Different Drug-Resistant Staphylococcus aureus Strains on the Physiological Properties of MAC-T Cells and Their Transcriptome Analysis - Yan, Lijiao; Yang, Yuze; Ma, Xiaojun; Wei, Lianhua; Wan, Xuerui; Zhang, Zhao; Ding, Jucai; Peng, Jie; Liu, Guo; Gou, Huitian; Wang, Chuan; Zhang, Xiaoli (Frontiers in Veterinary Science, 2022)
Staphylococcus aureus (S. aureus) is one of the main pathogens causing mastitis in dairy cows. The current work mainly focuses on the pathway of apoptosis induction in MAC-T cells caused by S. aureus infection or other factors. However, it is unknown that the physiological characteristics and mRNA expression of MAC-T cells infected with diverse drug-resistant S. aureus. MRSA (methicillin-resistant S. aureus) and MSSA (methicillin-susceptible S. aureus) were used to infect MAC-T cells in order to investigate this issue. The adhesion, invasion and apoptosis ability of MRSA-infected, MSSA-infected was assessed throughout the time (2h, 4h, 6h, 8h and 12h). After 8 hours, RNA sequencing was conducted on MRSA-infected and MSSA-infected with uninfected MAC-T cells as controls. The results showed that the adhesion and invasion ability of MRSA-infected and MSSA-infected to MAC-T cells increased and then decreased with infection time, peaking at 8 hours. Adhesion and invasion rates of MSSA-infected were substantially lower than MRSA-infected, and the invasion rate of MSSA-infected was nearly nonexistent. And the apoptosis rate of MAC-T cells increased as infection time increased. Transcriptome analysis revealed 549 differentially expressed mRNAs and 390 differentially expressed mRNAs in MRSA-infected and MSSA-infected MAC-T cells, respectively, compared to uninfected MAC-T cells. According to GO analysis, these differentially expressed genes are involved in immune response, inflammation, apoptosis, and other processes. KEGG indicated that AMPK pathway, FOXO pathway, HIF-1 pathway, IL-17 pathway, JAK-STAT pathway, MAPK pathway, mTOR pathway, NF-kappa B pathway, p53 pathway, PI3K-Akt pathway, TNF pathway, Toll-like receptor pathway, Rap1 pathway, RAS pathway, prion disease pathway, bacterial invasion of epithelial cells pathway were linked to adhesion, invasion inflammation and apoptosis. We found 85 DEGs from 42 KEGG-enriched pathways associated with adhesion, invasion, apoptosis and inflammation, all of which are implicated in MAC-T cell resistance to MRSA and MSSA infection. This study would offer helpful data for the effect of different drug-resistant S. aureus on dairy cow mammary epithelial cells and aid in the prevention of mastitis in the dairy industry.